Cardiac magnetic resonance features of acute myocarditis presenting as acute coronary syndrome. (25th November 2020) - Szabo, L; Bagonyi, A; Dohy, Z.S; Czimbalmos, C.S; Toth, A; Suhai, F.I; Juhasz, V; Horvath, V; Becker, D; Merkely, B; Vago, H
Abstract: Background: Clinical presentation of myocarditis varies, one specific form of myocarditis appears with the clinical signs of acute coronary syndrome (ACS). Cardiac magnetic resonance (CMR) is an important method for assessing ventricular function and morphology, additionally provides accurate tissue specific and functional information of the heart. Aims: Our aim was to investigate the characteristics, and prognosis of myocarditis presenting with ACS symptoms. Methods: 113 patients with the clinical signs of ACS but nonobstructed coronary arteries in whom the CMR revealed acute myocarditis were included in our study. CMR was performed in acute phase and at 3–6-month follow-up. Left ventricular (LV) volumes, mass and strain parameters expressing myocardial deformity were determined. Additional images were taken to represent tissue specific information. Relationships between laboratory and CMR parameters were investigated. Parameters predicting changes in LV ejection fraction (LVEF) were analyzed by logistic regression. Results: A total of 113 patients with myocarditis (98 males, 31±11 years) underwent acute and follow-up CMR. Sixty two patients reported fever or infection before the beginning of their complaints, most commonly gastroenteritis (33%) and pharyngitis (32%). The creatinine kinase MB value measured in the acute phase showed positive correlation with the extent of necrosis, and the global longitudinal- and circumferential strain. The extent of the LV necrosis showed negative correlation with LVEF and positive correlation with global circumferential strain (GCS) (p<0.05). On the control CMR examination LVEF and all global strain values improved, fibrosis persisted in 82% of cases but shrank (15±11 vs 5±4 g) and LV mass decreased (p<0.01) compared to the acute phase. Compared to the acute phase, 21% of the patients had lower LVEF on the follow-up CMR. Lower initial LVEF, worse acute GCS, and greater LV necrosis were independent predictors of LVEF reduction in the logistic regression model. During a median follow-up of 6-years of patients treated at our clinic (n=39) no patient suffered cardiac death, heart failure, or documented ventricular arrhythmia but 21% of them had recurrent myocarditis. Conclusion: Myocarditis mimicking ACS affects predominantly young men and shows functional improvement and good prognosis on follow-up, but it may reoccur in some cases. The reduction of LV function on control CMR may be predicted by worse initial LVEF, GCS, and a larger LV scar. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Project no. NVKP_16-1-2016-0017 has been implemented with the support provided from the National Research, Development and Innovation Fund of Hungary, financed under the NVKP_16 funding scheme. This project was supported by a grant from the National Research, Development and Innovation Office (NKFIH) of Hungary (K 120277).